2006
DOI: 10.1016/j.learninstruc.2006.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process-oriented worked examples on troubleshooting transfer performance

Abstract: In the domain of electrical circuits troubleshooting, a full factorial experiment investigated the hypotheses that a) studying worked examples would lead to better transfer performance than solving conventional problems, with less investment of time and mental effort during training and test, and b) adding process information to worked examples would increase investment of effort during training and enhance transfer performance; whereas adding it to conventional problems would increase investment of effort, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 29 publications
10
133
0
6
Order By: Relevance
“…In line with the finding that imitation does not seem to be necessary for learning, worked examples research has demonstrated that studying examples only is also more effective for learning than engaging in problem solving only (Nievelstein et al 2010;Van Gerven et al 2002;Van Gog et al 2006). In fact, it can be questioned whether the opportunity to practice indeed has added value for learning: A recent study found that both examples only and example-problem pairs were more effective than problem solving and problem-example pairs, and there was no significant difference between examples only and example-problem pairs .…”
Section: How Should Examples Be Delivered To Optimize Their Effectivementioning
confidence: 73%
See 3 more Smart Citations
“…In line with the finding that imitation does not seem to be necessary for learning, worked examples research has demonstrated that studying examples only is also more effective for learning than engaging in problem solving only (Nievelstein et al 2010;Van Gerven et al 2002;Van Gog et al 2006). In fact, it can be questioned whether the opportunity to practice indeed has added value for learning: A recent study found that both examples only and example-problem pairs were more effective than problem solving and problem-example pairs, and there was no significant difference between examples only and example-problem pairs .…”
Section: How Should Examples Be Delivered To Optimize Their Effectivementioning
confidence: 73%
“…Recent studies have shown, however, that adding worked examples to tutored problem-solving environments (worked examples: Schwonke et al 2009;videobased modeling examples: McLaren et al 2008) or realistic mathematics methods (Van Loon-Hillen et al in press) can also enhance learning, reduce acquisition time, or both. In addition, worked examples have been found to be more effective for learning than discovery learning (Tuovinen and Sweller 1999) and problem solving with a more general level of guidance provided by process steps (i.e., a description of the steps to be taken, but the steps are to be worked out by the learner; Nievelstein et al 2010;Van Gog et al 2006).…”
Section: Why Is Example-based Learning Effective?mentioning
confidence: 99%
See 2 more Smart Citations
“…Given our own prior results [8], which showed better learning efficiency in alternating examples/tutored problems versus all tutored problem solving, as well as the preponderance of evidence supporting the advantages of the two-step learning process [3,4,5,6], the first part of this hypothesis (i.e., alternating examples/tutored problems > all tutored problems) was already well supported. Despite some (but limited) evidence that all examples can be more effective for learning and more efficient in mental effort, at least as compared to all untutored problem solving [9,10], our theory was that all examples might be faster than examples/tutored problems but likely at the expense of careful study and robust learning, thus hurting both learning outcome and efficiency, suggesting the second part of our hypothesis (i.e., alternating examples/tutored problems > all worked examples). On the other hand, an "in press" study, one that occurred more-or-less concurrently to ours (yet after our hypothesis was formulated), casts doubt on the notion that an alternating condition is better than all examples, at least with respect to regular, non-tutored problem solving.…”
Section: Introductionmentioning
confidence: 99%